The Concept of Fiqh Al-Bi’ah Toward Environmental Sustainability Post Pandemic Covid-19 - Aminah, Siti (TAHKIM, 2022)
The transmission of the Covid-19 outbreak has resulted in a significant increase in waste production in various parts of the world. Medical waste and online shopping waste contribute to the garbage. The vast majority of the trash will be dumped into the sea. This can harm seafloor ecosystems and biodiversity. Furthermore, waste has impacted many aspects of life, including the social, economic, health, and environmental sectors and political issues. As a result, this research aims to put the concept of Fiqh al-bi'ah into practice to solve these problems. This study employs a literature review method that includes books, journals, articles, and related writings. According to the findings of this study, the concept of fiqh al-bi'ah can be used to reduce the amount of waste generated during a pandemic outbreak. The surrounding community and government must comprehend and inspire the provisions of the fiqh al-bi'ah concept's six points. Increasing environmental knowledge and awareness based on Islam must be widely echoed. Increased spiritual-based human resources may impact the quality of equilibrium and ecological conservation. In essence, religious moral teachings and environmental ethics are inextricably linked. This corresponds to increased waste accumulation related to online shopping habits and ineffective medical waste management. As a result, the real action offered by the fiqh al-bi'ah concept is to switch to environmentally friendly products. Furthermore, the younger generation must be instilled with environmental education regarding Fiqh al-bi'ah.Keywords       : Fiqh al-bi’ah, covid-19, environmental sustainability